Efektivitas Dan Efisiensi Sistem Pembayaran Non Tunai Quick Response Code Indonesian Standard (QRIS) Dalam Mempengaruhi Inklusi Keuangan Nasabah Pt. Bank Rakyat Indonesia (Persero) Tbk Di Kc Kota Bengkulu - Tri Hayunda, Namira; Arifah Hidayati; Veny Puspita (STEKOM PRESS, 2023)
The study intends evaluate impact PT BankRakyat Indonesia (PERSERO) TBK's Bengkulu City Branch Office's QuickResponse Code Indonesian Standard (QRIS) Non-Cash PaymentSystem on financial inclusion (Y). by employing quantitative techniques. The primary data utilized this study were obtained by handing out questionnaires to Bank Rakyat Indonesia (PERSERO) Tbk clients at the Bengkulu City Branch Office. Test multiple linear regression analysis from the constant value coefficients table 36.448 it can be explained a positive correlation between Effectiveness (X1) and the coefficient, indicating Effectiveness on Financial Inclusion. The effectiveness variable is 0.811, meaning that if the other independent variables are constant, then there is an increase of 1 unit, so financial inclusion will increase by 0.811, the coefficient is positive. Test multiple linear regression analysis from the coefficients table with a constant value of 36.448, may be said that a positive coefficient indicates positive association between efficiency and financial inclusion the efficiency (X2) to financial inclusion has change value zero. The efficiency variable's value for regression coefficient 0.542, meaning that if the other independent variables remain the same, Financial Inclusion will increase by 1 unit, so Financial Inclusion will increase. The findings of the analysis's multiple correlation coefficient test X1, X2 affect Financial Inclusion (Y) of 0.936, which means that it has a very strong correlation coefficient relationship because value is in range between 0.80-1,000.